Mechanisms of ROS-induced mitochondria-dependent apoptosis in Phaeodactylum tricornutum under AgNPs exposure - Zhang, Yunfei; Liu, Caili; Li, Bin; Chen, Lizhu; Xiang, Zhiwei; Tian, Xiuhui; Sun, Chunxiao; Gao, Jiqing; Qiao, Ruiguang; Hu, Shunxin (Frontiers in Marine Science, 2024)
Nanomaterials such as silver nanoparticles (AgNPs) have gained widespread application across various fields. However, the large-scale production and application of AgNPs have raised concerns about their distribution in the environment and potential pollution issues. This study investigates the toxic effects of AgNPs on the diatom Phaeodactylum tricornutum by employing electron microscopy for cellular observation, quantifying apoptotic cell numbers, and measuring antioxidant indicators. The research examines how varying concentrations of AgNPs induce stress in P.